2016
DOI: 10.3748/wjg.v22.i7.2195
|View full text |Cite
|
Sign up to set email alerts
|

Role of regulatory T cell in the pathogenesis of inflammatory bowel disease

Abstract: Regulatory T (Treg) cells play key roles in various immune responses. For example, Treg cells contribute to the complex pathogenesis of inflammatory bowel disease (IBD), which includes Crohn's disease and ulcerative colitis during onset or development of that disease. Many animal models of IBD have been used to investigate factors such as pathogenic cytokines, pathogenic bacteria, and T-cell functions, including those of Treg cells. In addition, analyses of patients with IBD facilitate our understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 127 publications
3
118
2
2
Order By: Relevance
“…These results are consistent with recent reports from human studies demonstrating decreased levels of Tregs within the lamina propria of the intestine of premature infants afflicted with NEC (23). Interestingly, the balance between these two opposing cell populations has been shown to be of critical relevance in the development of autoimmunity (27) and inflammatory bowel disease (28) further demonstrating the relevance of these cell populations in health and disease. Strikingly, this imbalance can be modulated by enteral administration of the vitamin A metabolite, retinoic acid (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with recent reports from human studies demonstrating decreased levels of Tregs within the lamina propria of the intestine of premature infants afflicted with NEC (23). Interestingly, the balance between these two opposing cell populations has been shown to be of critical relevance in the development of autoimmunity (27) and inflammatory bowel disease (28) further demonstrating the relevance of these cell populations in health and disease. Strikingly, this imbalance can be modulated by enteral administration of the vitamin A metabolite, retinoic acid (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that immune cells play a role in controlling inflammation in the colon [24]. Among these immune cells, Tregs have been described as having important roles in regulating the pathogenesis of IBD [25,26], and the balance between Tregs and other T cells in the intestinal tract is known to influence IBD pathogenesis [27].…”
Section: Previous Studies Have Shown That Stem Cells Affect Recipientmentioning
confidence: 99%
“…For example, in the gut, where constant pathogen interaction occurs, Tregs prevent development of colitis. The loss of this anti-inflammatory mechanism has been shown to play a significant role in inflammatory bowel disease (IBD) [110]. Sun et al found that DCs in the lamina propria of the small intestine drive the maturation of Tregs from CD4+ T helper cells [111].…”
Section: Mechanisms Of Hif-1α Stabilization Activation and Degradatmentioning
confidence: 99%